Correction: Preparation and property investigation of chain end functionalized cis-1, 4 polybutadienes via de-polymerization and cross metathesis of cis-1, 4 polybutadienes. Issue 32 (1st August 2019) - Ying, Weilun; Pan, Weijing; Gan, Qiao; Jia, Xiaoyu; Grassi, Alfonso; Gong, Dirong
Abstract : Correction for 'Preparation and property investigation of chain end functionalized cis -1, 4 polybutadienes via de-polymerization and cross metathesis of cis -1, 4 polybutadienes' by Weilun Ying et al., Polym. Chem., 2019, 10, 3525–3534.